2014
DOI: 10.1007/s00464-014-3889-8
|View full text |Cite
|
Sign up to set email alerts
|

ERCP using a short double-balloon enteroscope in patients with prior pancreatoduodenectomy: higher maneuverability supplied by the efferent-limb route

Abstract: The short DBE facilitates ERCP in prior-PD patients. Particularly, ERCP using the efferent-limb route can achieve a maneuverable procedure without unnecessary stress, such as scope insertion to the sharp-angled afferent limb and the handling of various accessories through the narrow scope channel with a sense of resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…14 Table 3 shows the outcomes of short-type DBE-assisted ERCP in patients with SAA. 9,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The success rates of reaching the target site, biliary cannulation, and therapeutic procedure in short-type DBE-assisted ERCP were 94.8%, 95.6%, and 94.5%, respectively, from these pooled data. On the other hand, the latest systematic review and meta-analysis reported that the success rates of reaching the target site, biliary cannulation, and therapeutic procedure in both short-type and standardtype DBE-assisted ERCP were 90%, 94%, and 93%, respectively.…”
Section: Short-type Double Balloon-assisted Ercpmentioning
confidence: 87%
“…14 Table 3 shows the outcomes of short-type DBE-assisted ERCP in patients with SAA. 9,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The success rates of reaching the target site, biliary cannulation, and therapeutic procedure in short-type DBE-assisted ERCP were 94.8%, 95.6%, and 94.5%, respectively, from these pooled data. On the other hand, the latest systematic review and meta-analysis reported that the success rates of reaching the target site, biliary cannulation, and therapeutic procedure in both short-type and standardtype DBE-assisted ERCP were 90%, 94%, and 93%, respectively.…”
Section: Short-type Double Balloon-assisted Ercpmentioning
confidence: 87%
“…Two endoscopic approaches (the afferent-limb route and efferent-limb route) are possible for HJ anastomosis in patients with Braun anastomosis, and we usually selected the efferent-limb route because it allows accurate identification of the route to the HJ anastomosis. That is, selection of the middle of a three-pronged lumen at the Braun anastomosis for the route leads the scope to the HJ anastomosis and allows for better maneuverability [ 7 ]. After reaching close to the blind end of the jejunum, endoscopic visualization of the pinpoint orifice or cicatricial mucosa was attempted to identify the HJ anastomosis, sometimes using fluoroscopic guidance (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Table 3 shows the outcomes of DBE-assisted ERCP procedures in patients with SAA [29][30][31][32][33][34][35][36][37][38]. The latest systematic review and meta-analysis reported that the pooled data reaching the target site, biliary cannulation, and procedural success rates were 90%, 94%, and 93%.…”
Section: Double Balloon-assisted Ercpmentioning
confidence: 99%